Generation of Atmospheric Pressure Plasma by Repetitive Nanosecond Pulses in Air Using Water Electrodes - 邵涛 于洋 章程 姜慧 严萍 周远翔 (Plasma science & technology, 2011)
Dielectric barrier discharge （DBD） excitated by pulsed power is a promising method for producing nonthermal plasma at atmospheric pressure. Discharge characteristic in a DBD with salt water as electrodes by a home-made unipolar nanosecond-pulse power source is presented in this paper. The generator is capable of providing repetitive pulses with the voltage up to 30 kV and duration of 70 ns at a 300 Ω resistive load. Applied voltage and discharge current are measured under various experimental conditions. The DBD created between two liquid electrodes shows that the discharge is homogeneous and diffuse in the whole discharge regime, Spectra diagnosis is conducted by an optical emission spectroscopy. The air plasma has strong emission from nitrogen species below 400 nm, notably the nitrogen second positive system.